Recent advances in food and flavor chemistry : food flavors and encapsulation, health benefits, analytical methods, and molecular biology of functional foods - Ho, Chi-Tang, 1944- (Special publication (Royal Society of Chemistry (Great Britain)) ;, 2010)
"This book is the Proceedings of the 12th International Flavor Conference, 4th George Charalambous Memorial Symposium, held May 25-29, 2009 in Skiathos, Greece. The International Flavor Conferences are sponsored by the Agricultural Food Chemistry Division of the American Chemical Society and are attended by leaders in the in the field of flavor and food chemistry. The International Flavor Conferences have been held as a global forum for leaders in the field of flavor and food chemistry to present their results covering recent research activities. As in previous years the conference stresses flavors as its main theme but also includes important topics in food chemistry (analytical methods, packaging storage) and production (safety, patents). Information gathered by researchers in food chemistry have found numerous practical applications for improving foods, and symposia such as this have a goal of transferring basic knowledge to finished products. Recent Advances in Food and Flavor Chemistry: Food Flavors and Encapsulation, Health Benefits, Analytical Methods, and Molecular Biology of Functional Foods will be a useful reference for researchers and other professionals in the industry and academia, particularly those involved directly in food science. This book covers several topical areas and includes: -A historical look at the use of isotopic analyses for flavour authentication -Computer-aided organic synthesis as a tool for generation of potentially new flavouring compounds from ascorbic acid -Butter flavors and microwave popcorn: A review of health issues and industry actions -The aroma of guavas - Key aroma compounds and influence of tissue disruption -Flavour release in lipid rich food matrices; in vitro and in vivo measurement using proton transfer reaction mass spectrometry -A study of the fate of aspartame and flavour molecules in chewing gum utilizing LC/MS/MS and GC/MS -Study on the interaction of selected phenolic acids with bovine serum albumin"--EBL.